Modern Sufis and the State: The Politics of Islam in South Asia and Beyond, edited by Katherine Pratt Ewing and Rosemary R. Corbett. - Parciack, Ronie (Religions of South Asia, 2022)
Modern Sufis and the State: The Politics of Islam in South Asia and Beyond, edited by Katherine Pratt Ewing and Rosemary R. Corbett. New York: Columbia University Press, 2020. 360 pp., £108 (hb), £28 (pb). ISBN 9780231195744 (hb), 9780231195751 (pb).